Effects of Corporate Social Responsibility on Capital Market and Firm Performance (British Journal of Multidisciplinary and Advanced Studies, 2024)
This study examines the relationship between corporate social responsibility in the Capital market and the firm performance of quoted companies in Nigeria with Seplat Energy Plc as a case study. The study made use of an ex-post facto research design. This research adopted the annual reports of Seplat Energy Plc covering the period of 2014-2020. CSR was measured using the donations made by the company, while financial performance was measured using net profit margin, return on equity, and return on assets. Data were analysed using simple linear regression analysis with the aid of SPSS version 25. It was discovered that CSR has a negative and insignificant effect on NPM, positive but insignificant effect on ROE, positive but insignificant effect on ROA, positive but insignificant effect on SP. It was recommended that Nigerian corporate organisations establish a social responsibility unit to ensure that organisation responsive to social responsibility aligns with international best practice. Also, the government must establish an agency to monitor corporate organisations' social responsibility to oversee CSR policy compliance and prosecute socially irresponsible organisations.